Development of qPCR and ddPCR-based diagnostic tools for detection and quantification of Apiospora marii - Incampo, Giuseppe (Plant disease, 2025)
Apiospora marii (syn.= Arthrinium marii) is an ascomycete recently associated to olive tree dieback in Italy and Spain. With this study, a quantitative qPCR and a digital droplet ddPCR were developed for its detection. Considering the sequences available in GenBank, the ITS region was selected, and two primers/probe sets (AM135 and AM158) were generated. The optimization of the PCR conditions showed that 60°C was the best annealing temperature and 500/250 nM the best primers/probe concentration in both assays. Under these conditions, 1 fg µL-1 of A. marii DiSSPA_A1 DNA was detectable by qPCR corresponding to Cq 32 for AM135 and 33 for AM158. The same concentration was the lowest detected in ddPCR corresponding to 0.20 and 0.12 c µL-1, respectively for AM135 and AM158. The specificity of both primers/probe sets was tested in qPCR and ddPCR using the DNA of microorganisms commonly associated with olive wood and different olive cultivars. Untargeted amplifications were observed using the DNA of some isolates, and consequently the PCR reaction was stopped at the 37th cycle. The primer/probe set AM158 showed the best performance, and it was used for the validation in qPCR and ddPCR using the DNA extracted from healthy, artificially inoculated, and field naturally infected olive trees. Both positive amplification and A. marii-colonies were always obtained from samples artificially inoculated and from field naturally infected olive trees. The diagnostic tools can be used for monitoring A. marii and will be particularly helpful for evaluations on plant propagation material and to investigate aspects of the fungus lifestyle